Speeches on Poetry - Max Deutscher (Philosophies)
Paul Celan’s ‘Speeches’ determine what poetry is and why we need it. He does not want ‘timeless’ poetry but still ‘lays claim to infinity’; he would ‘reach through time’. He neither refuses poetry as contrary to reason, nor elevates it as pure immediacy of meaning. He questions the ambivalent attitudes towards art—as ‘artifice’ or as ‘profound’. Celan cuts into the loose fabric of such ordinary language to shape it. Those who trumpet ‘plain sense’ against such incisive art deface it as degenerate. Celan’s poetic language presents us as ‘of the earth’ and as ‘released from it’—Büchner’s Lenz seeks clarity in the silence of alpine light but falls into madness in his isolation. He is drawn towards the life of the villagers at the foot of the mountains. He perceives the warm household fires, but it is an illusion that he can be a part of that scene. Thus, Celan enquires into art’s intensity. It is at the risk of reciprocity that a reader entertains the language of a poem. Eliot’s old ‘shadow’ between ‘the idea and the reality’ now falls between the poet’s production and the reader’s reciprocation. The reader may need someone with a free hand to hold a lantern to the script.